Optimizing Small Excavator Maintenance Activity Planning Using the Reliability-Centered Maintenance (RCM) Method II - Imah Luluk Kusminah; Aulia Nadia Rachmat; Diah Ayu Nurjanah (International Journal of Marine Engineering Innovation and Research, 2024)
Construction activities include the stages of construction, operation, maintenance, demolition, and rebuilding of a building. One of the construction activities in Indonesia is the construction of double-track railways. In the double-track railway construction project, there is a small excavator A which often fails. The excavator is used for excavation, land stripping, and embankment work. Failures that occur can disrupt construction implementation and can result in the company experiencing losses. Maintenance activities in the construction company that is the research location have a maintenance schedule, namely every 3 months and every 6 months based on the manual book, without adjusting the condition of the equipment. Therefore, it is necessary to analyze excavator components so that appropriate maintenance is known. RCM II is a maintenance evaluation method so that system components run well and according to the expected function by determining a maintenance action that must be carried out based on the characteristics of machine use so that maintenance activities run optimally. This research uses the RCM II method to determine the maintenance schedule, as well as the FMEA method. The FMEA results show 43 failure modes. RCM II decision worksheet analysis showed that 8 components had scheduled discard task maintenance, 3 components had scheduled restoration task maintenance, and 1 component had scheduled on-condition task maintenance.